2014
DOI: 10.1002/cmdc.201400017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anti‐tubulin and Antiproliferative SAR of Steroidomimetic Dihydroisoquinolinones

Abstract: A SAR translation strategy adopted for the discovery of tetrahydroisoquinolinone (THIQ)-based steroidomimetic microtubule disruptors has been extended to dihydroisoquinolinone (DHIQ)-based compounds. A steroid A,B-ring-mimicking DHIQ core was connected to methoxyaryl D-ring mimics through methylene, carbonyl, and sulfonyl linkers, and the resulting compounds were evaluated against two cancer cell lines. The carbonyl-linked DHIQs in particular exhibit significant in vitro antiproliferative activities (e.g., 6-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…1,2,3,4-Tetrahydroisoquinoline (THIQ) motifs are present in many natural alkaloids [ 1 ]. THIQ derivatives have also been investigated as potential therapeutics in a wide range of diseases and recent studies have explored their potential as steroidomimetics [ 2 5 ]. Given the success of these authors in designing highly potent non-steroidal chimeric microtubule disruptors based upon decorated THIQ-based mimics of the steroidal AB ring system that possess pendant N- substituents [ 2 ], robust routes to direct N- aryl substituted THIQs were targeted for related activities ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4-Tetrahydroisoquinoline (THIQ) motifs are present in many natural alkaloids [ 1 ]. THIQ derivatives have also been investigated as potential therapeutics in a wide range of diseases and recent studies have explored their potential as steroidomimetics [ 2 5 ]. Given the success of these authors in designing highly potent non-steroidal chimeric microtubule disruptors based upon decorated THIQ-based mimics of the steroidal AB ring system that possess pendant N- substituents [ 2 ], robust routes to direct N- aryl substituted THIQs were targeted for related activities ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the strong acid in high concentration led to the formation of carbamate dicataion, which is dissociated to the protonated isocyanate which further cyclized to 3,4-dihydroisoquinolin-1(2H)-one (Scheme 1). [24] Additionally, the same research group demonstrated that the phenyl ethyl carbamate bearing ortho salicylate (13) as an ether group accelerates the rate for the formation of the protonated isocyanate which underwent subsequent electrophilic cyclization to 3,4-dihydroisoquinolin-1(2H)-one. They found out ortho salicylate helps in accelerating the CÀ O bond dissociation which facilitates the formation of the isocyanate cation.…”
Section: Intramolecular Cyclization Of Carbamate/ Urea/ Thiourea/ Isomentioning
confidence: 99%
“…3,4-Dihydroisoquinolin-1(2H)-one core containing compounds possess wide range of biological activities such as anti-HIV, [7] antidepressant, [8] anticancer, [9] H3 receptor antagonist for treatment of neuropathic pain, [10] EZH2 inhibitor, [11] PARP inhibitor, [12] steroidomimetic, [13] cyclin-dependent kinase inhibitor, [14] anti-hypertension, anti-arrhythmia, antioxidant, [15] inhibitor of cholesterol biosynthesis, [16] anti-thrombotic, [17] antiinflammatory, [8] antibacterial, [18] PET imaging of s2 receptors. [19] The molecular structure of representative 3,4-dihydroisoquinolin-1(2H)-one's of biological importance is illustrated in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the antitubulin and antiproliferative activities of C3/C1-substituted THIQs 9 ( Figure 2) depend on the pharmacophore group at C6 (as free phenol or sulfamate group) [32][33][34]. Therefore, procedures of the benzyl protection/deprotection of phenolic groups have been employed in the literature showing in many cases some incompatibility with the other functional groups present on the THIQ skeleton [33].…”
Section: Introductionmentioning
confidence: 99%